Early-life exposure to tobacco smoke alters airway signaling pathways and later mortality in D. melanogaster. (15th September 2022) - Sirocko, Karolina-Theresa; Angstmann, Hanna; Papenmeier, Stephanie; Wagner, Christina; Spohn, Michael; Indenbirken, Daniela; Ehrhardt, Birte; Kovacevic, Draginja; Hammer, Barbara; Svanes, Cecilie; Rabe, Klaus F.; Roeder, Thomas; et al.
Abstract: Early life environmental influences such as exposure to cigarette smoke (CS) can disturb molecular processes of lung development and thereby increase the risk for later development of chronic respiratory diseases. Among the latter, asthma and chronic obstructive pulmonary disease (COPD) are the most common. The airway epithelium plays a key role in their disease pathophysiology but how CS exposure in early life influences airway developmental pathways and epithelial stress responses or survival is poorly understood. Using Drosophila melanogaster larvae as a model for early life, we demonstrate that CS enters the entire larval airway system, where it activates cyp18a1 which is homologues to human CYP1A1 to metabolize CS-derived polycyclic aromatic hydrocarbons and further induces heat shock protein 70. RNASeq studies of isolated airways showed that CS dysregulates pathways involved in oxidative stress response, innate immune response, xenobiotic and glutathione metabolic processes as well as developmental processes (BMP, FGF signaling) in both sexes, while other pathways were exclusive to females or males. Glutathione S-transferase genes were further validated by qPCR showing upregulation of gstD4, gstD5 and gstD8 in respiratory tracts of females, while gstD8 was downregulated and gstD5 unchanged in males. ROS levels were increased in airways after CS. Exposure to CS further resulted in higher larval mortality, lower larval-pupal transition, and hatching rates in males only as compared to air-exposed controls. Taken together, early life CS induces airway epithelial stress responses and dysregulates pathways involved in the fly's branching morphogenesis as well as in mammalian lung development. CS further affected fitness and development in a highly sex-specific manner. Graphical abstract: Image 1 Highlights: Early life exposure to cigarette smoke (CS) is related to later airway diseases. In D. melanogaste r larval airways CS induces an oxidative stress response. CS sex-specifically deregulates airway developmental and immune pathways. This is connected to higher mortality until adulthood in male flies only. The model offers a novel platform to study how early life CS links to airway disease.